Pharmacoepidemiological survey of schizophrenia in a tertiary care teaching hospital - Barman, Sarajita; Roy, Dolly; Yashin, Ali N. N.; Ghosh, Prosenjit (International Journal of Basic & Clinical Pharmacology, 2019)
Background: Prevalence of chronic schizophrenia is somewhat less than 1% of the population but this is one of the most important psychiatric illness due to its early onset, chronicity and associated disability. Methods: A prospective and observational study was carried out on 76 patients for 12 months. Patients of either sex, aged between 18 to 50 years who were diagnosed as schizophrenia according to DSM IV-TR were screened and recruited for the study. Prescriptions were analyzed for socio demographic details and psychotropic drugs prescribed. Results: Out of 76 patients 46 (60.53%) were males, maximum occurred 19 (41.30%) between 18 and 25 years of age. Females were 30 (39.47%), maximum occurred 12 (40%) between 34 - 39 years of age. 52 (68.42%) were from urban area and 24 (31.57%) were from rural area. 26 (34.21%) were illiterate, 24 (31.58%) primary educated, 16 (21.05%) secondary educated and 10 (13.16%) higher secondary and above. 20 (26.32%) were unemployed, students 9 (11.84%), housewives 19 (25%), agricultural workers 10 (13.16%), nonagricultural outdoor workers 4 (5.26%) and nonagricultural indoor workers were 14 (18.42%). Only atypical antipsychotics were prescribed .Olanzapine was prescribed in 30 (39.47%), risperidone 16 (21.05%), amisulpride 13 (17.11%), aripiprazole 11 (14.47%) and quetiapine 06 (7.89%) respectively. Conclusions: The sociodemographic factors associated with schizophrenia are urban locality, illiteracy, low socioeconomic status and unemployment. The treatment pattern observed correlates with the changing trends in the treatment of schizophrenia worldwide.